Cyto and genotoxicity induced by exposure to textile production effluents on Astyanax lacustris (Pisces: Characidae) can be reduced after treatment through a vertical flow constructed wetland system - Josiane Rodrigues Rocha da Silva; Cleiton Campos da Silva; Layon Zafra-Lemos; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Neotropical Ichthyology, 2025)
Abstract Textile effluents possess a complex composition that includes physical, chemical, and biological elements, and they may exhibit mutagenic, genotoxic, and carcinogenic properties. A portion of the dyes utilized in the textile industry is lost during the dyeing process, ultimately contaminating aquatic environments when released into bodies of water. Thus, the objective of this study was to assess the cyto/genotoxic effects of textile production effluents on Astyanax lacustris specimens both before and after treatment with a vertical flow constructed wetland system (VFCW). We examined 60 fish (divided into five treatment conditions, with four fish per condition, in triplicate). The fish were exposed to the contaminants for a duration of seven days. The analysis methods employed included biomarker assessment, the micronucleus (MN) test, cellular morphological changes (CMC) analysis, and the comet assay. Fish exposed to 5% v/v of raw textile effluent and the effluents that underwent VFCW treatment exhibited significant damage in comparison to the control groups. The bioremediation of the dye carried out by the VFCW system proved to be efficient, as confirmed by physicochemical analysis. We conclude that the biodegradation of textile production effluents can successfully be achieved through the use of VFCW.